The Concept of the Financial System in the Digital Economy - Ekaterina P. MOCHALINA; Galina V. IVANKOVA; Oleg V. TATARNIKOV; Valery A. TITOV (Communications of International Proceedings, 2020)
The work is devoted to the development of the financial system and its institutions under the conditions of digitalization of the economy. Banks and their development prospects under the influence of the digital economy were also considered. Moreover, the advantages and disadvantages of using tools such as White Label and Big Data have been studied. There was considered a new financial institution - Fintech.
Keywords: Fintech; digitalization; Big Data.